Valuation drinking water firms through real options - Gutiérrez Urzúa, Mauricio (2016)
Valuation a company represents a major challenge since it is necessary to incorporate various risk factors to determine their "fair" value. The real options method show stock price for Aguas Andinas company, around $ 473 (U$ 0.68) per share, higher than the historical result of the action. A review of market reports reveals confidence in this company, based on its investment plan and business projections. The results show that real options methodology generates additional value, mainly due to the positive impact of the risk on the value of the action and the variability of income. The methodology of real options requires further investigation, for a final decision.